Iatrogenic bladder injury following gynecologic and obstetric surgery: A systematic review and meta‐analysis - Ann‐Sophie Jensen; Ina Isabell Kathleen Heinemeier; Jeppe Bennekou Schroll; Martin Rudnicki (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction Iatrogenic bladder injury is a rare complication following obstetric and gynecologic surgery and only sparse information is available regarding length of transurethral catheterization following injuries, suturing techniques including choice of suture, and complications. The primary aim of this systematic review was to evaluate length of transurethral catheterization in relation to complications following iatrogenic bladder injury. Second, we aimed to evaluate the number of complications following repair of iatrogenic bladder injuries and to describe suture technique and best choice of suture. Material and methods A systematic review and meta‐analysis was conducted, and the results were presented in accordance with the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA) guidelines. PubMed, Embase, and Medline electronic databases were searched, and followed by screening from two independent reviewers. Studies published between January 2000 and March 2023 describing methods of bladder injury repair following obstetric or gynecologic benign surgery were included. Data extraction was done using Covidence. We performed a meta‐analysis on complications after repair and explored this with a meta‐regression analysis (Metafor package R) on length of catheterization to determine if length of catheterization influenced the risk of complication. A risk of bias tool from Cochrane was used to assess risk of bias and the study was registered in PROSPERO (CRD42021290586). Results Out of 2175 articles, we included 21 retrospective studies, four prospective studies, and one case‐control study. In total, 595 bladder injuries were included. Cesarean section was the most prominent surgery type, followed by laparoscopically assisted vaginal hysterectomy. We found no statistically significant association between length of transurethral catheterization and numbers of complications following repair of iatrogenic bladder injuries. More than 90% of injuries were recognized intraoperatively. Approximately 1% had complications following iatrogenic bladder injury repair (0.010, 95% confidence interval 0.0015–0.0189, 26 studies, 595 participants, I2 = 4%). Conclusions Our review did not identify conclusive evidence on the length of postoperative catheterization following bladder injury warranting further research. However, the rate of complications was low following iatrogenic bladder injury with a wide range of repair approaches.